Computed tomographic and radiographic morphometric study of cardiac and coelomic dimensions in captive blue-fronted Amazon parrots (Amazona aestiva, Linnaeus, 1758) with varying body condition scores - dos Santos, Gisele J. [UNESP]; da Silva, Jeana P. [UNESP]; Hippólito, Alícia G. [UNESP]; Ferro, Bárbara S. [UNESP]; Oliveira, Elton Luís R. [UNESP]; Okamoto, Priscylla Tatiana C. G. [UNESP]; Lourenço, Maria Lucia G. [UNESP]; de Vasconcelos Machado, Vania Maria [UNESP]; Rahal, Sheila C. [UNESP]; Teixeira, Carlos R. [UNESP]; Melchert, Alessandra [UNESP] (Wiley, 2020)
This study aimed to assess radiographic and tomographic cardiac parameters, including width and length of the heart, and the ratio of heart width to coelom width of blue-fronted Amazon parrots (Amazona aestiva) with varying body condition scores. Thirty-five captive birds were included in the study and were allocated into one of three groups according to their respective body condition score: lean, ideal and obese. No differences were observed among the groups with regard to radiographic and tomographic measurements. Computed tomography enabled better identification of the structures of the cardiovascular system without interference from the overlying structures of the celomatic cavity observed in radiographic images. However, radiographic examinations should still be considered the standard screening method to identify cardiac alterations, such as increased or reduced organ dimensions. Standardizing the techniques and measurements performed in this study may serve as a basis for further research in the field.
Keywords: cardiology; Psittacidae; radiography; tomography